Pre-clinical model of dysregulated FicD AMPylation causes diabetes by disrupting pancreatic endocrine homeostasis - Amanda K. Casey; Nathan M. Stewart; Naqi Zaidi; Hillery F. Gray; Hazel A. Fields; Masahiro Sakurai; Carlos A. Pinzon-Arteaga; Bret M. Evers; Jun Wu; Kim Orth (Molecular Metabolism)
The bi-functional enzyme FicD catalyzes AMPylation and deAMPylation of the endoplasmic reticulum chaperone BiP to modulate ER homeostasis and the unfolded protein response (UPR). Human hFicD with an arginine-to-serine mutation disrupts FicD deAMPylation activity resulting in severe neonatal diabetes. We generated the mFicDR371S mutation in mice to create a pre-clinical murine model for neonatal diabetes. We observed elevated BiP AMPylation levels across multiple tissues and signature markers for diabetes including glucose intolerance and reduced serum insulin levels. While the pancreas of mFicDR371S mice appeared normal at birth, adult mFicDR371S mice displayed disturbed pancreatic islet organization that progressed with age. mFicDR371S mice provide a preclinical mouse model for the study of UPR associated diabetes and demonstrate the essentiality of FicD for tissue resilience.